Ursodeoxycholic Acid in Intrahepatic Cholestasis of Pregnancy: A Systematic Review and Individual Participant Data Meta-analysis. Issue 9 (September 2021) - Ovadia, Caroline; Sajous, Jenna; Seed, Paul T.; Patel, Kajol; Williamson, Nicholas J.; Attilakos, George; Azzaroli, Francesco; Bacq, Yannick; Batsry, Linoy; Broom, Kelsey; Brun-Furrer, Romana; Bull, Laura; et al.
Abstract : (Abstracted from Lancet Gastroenterol Hepatol 2021;6:547–558) Ursodeoxycholic acid (UA) is a common treatment for intrahepatic cholestasis of pregnancy (ICP), and its use is supported by the Society for Maternal-Fetal Medicine. However, evidence of the benefit of UA to fetal and neonatal outcomes in this patient population is unclear.